Analisis Kinerja MySQL Cluster Menggunakan Metode Load Balancing - Taufiq Abdul Gani; Aulia Arafat; . Melinda (Universitas Syiah Kuala, 2015)
Information system and data is a very important thing nowadays. An information system especially a database is designed with a high data availability. One of the database systems is MySQL cluster. Sometimes, its performance decreased because of the system’s incapablity to handle the data. To overcome this problem, the research of load balancing systems for MySQL cluster is needed. This research is intended to analyze the effect of load balancing clustering methods on MySQL cluster which by default has been set as failover clustering. The analysis is done through data collection and database transactions test to get the number of Transactions per second (TPS) and response time parameter using SysBench. The test is divided into two main scenarios, the simple and complex-mode that running on 4 computers. The tests were conducted by giving workloads from 8 up to 128 threads respectively to the server through a client on default conditions and load balancing. The test results showed the number of TPS at MySQL cluster default is 536.61. In contrast, number of TPS at load balancing is better at 2261.22. Likewise, the response time at MySQL cluster load balancing is 147.55 ms faster than that of the default one at 335.00 ms.